Evaluation of alternative intra-oral repair techniques for fractured ceramic-fused-to-metal restorations - (:unkn) unknown (WILEY, 2003)
Ceramic fractures are serious and costly problems in dentistry. Moreover, they pose an aesthetic and functional dilemma both for the patient and the dentist. This problem has created demand for the development of practical repair options which do not necessitate the removal and remake of the entire restoration. Published literature on repair techniques for fractured fixed partial dentures, concentrating on the data obtained both from in vitro and in vivo studies, reveals that the repair techniques based on sandblasting and silanization are the most durable in terms of adhesive and cohesive failures compared with those using different etching agents.
Keywords: fracture; ceramics; intra-oral repair; TENSILE BOND STRENGTH; COMPOSITE RESIN; SURFACE-TREATMENT; ETCHED PORCELAIN; DENTAL PORCELAIN; TOPICAL FLUORIDE; AGENTS; SHEAR; SYSTEMS; CROWN